Review of methods and indicators in sustainable urban transport studies overview from 2000 to 2016 - Nadi, Puji Adiatna; Murad, AbdulKader (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2017)
The attention of countries either the developed or developing countries on sustainable urban transport is becoming more popular. The purpose of paper is to review the methods and the indicators used for measuring performance of sustainable urban transport. This study is based on the literature review and the case study observation and also uses the quantitative assessment. It reviews the theoretical aspects of sustainability factors at various research works and performance indicator in urban transportation. The indicators were classified into two major categories: (i) assessment methods in sustainable urban transport (SUT), and (ii) basic of sustainability indicators for urban transport. This study found several types of analytical techniques for measuring sustainability indicators in urban transport. It also identify five indicators as basic element to measure sustainable urban transport performance i.e. traffic congestion, traffic air pollution, traffic noise pollution, traffic accidents and land consumption for transport infrastructure.